Структуры континентальной и переходной земной коры на космических снимках - Филатова Н. И. Надежда Ивановна; Егоров И. В. Иван Владимирович; Дворянкин А. И. Александр Иванович; Дорогутин А. П. Андрей Павлович; Кузнецова И. А. Ирина Александровна (Москва, Недра, 1984)
Авторы указаны на обороте тит. л.